Teaching Small Group Communication: A Do Good Project - Elizabeth M. Minei, PhD (Park University, 2016)
This paper focuses on the parameters of a semester-long project called the "Do Good" project, geared towards developing small group communication skills in undergraduate students. This project highlights participation in a social engagement project that allows students to bridge concepts learned in small group communication lectures (e.g., team dynamics, project management, conflict resolution, decision making, leadership) with community outreach. Included are an overview of the project, and examples for how each component both challenges students' ability to communicate in groups and provides motivation that foster students' ability to link in-class knowledge with practical, real world application.